Construction management strategies : a theory of construction management - Radosavljevic, Milan 548684; Bennett, John, 1936- 431818 (Chichester, West Sussex, UK ; Ames, Iowa : Wiley-Blackwell, 2012)
Includes bibliographical references and index.